Hydroalcoholic Extract of Sechium edule Fruits Attenuates QT Prolongation in High Fat Diet-Induced Hyperlipidemic Mice. (11th July 2022) - Mohammed, Firdous Sayed; Ghosh, Arya; Pal, Sourav; Das, Chayan; Alomar, Suliman Yousef; Patwekar, Mohsina; Patwekar, Faheem; Jeon, Byong-Hun; Islam, Fahadul
Abstract : The present study aimed to evaluate the effect of hydroalcoholic extract of Sechium edule (S.E.) fruits on lipid profile and electrocardiogram (ECG) parameters in high fat-diet (HFD) induced hyperlipidemic mice. In this study, grouping of animals was done as described below ( n  = 6), where group 1 is normal control, group 2 is HFD control, group 3 is HFD + atorvastatin (10 mg/kg), group 4 is HFD + S.E. extract (200 mg/kg), and group 5 is HFD + S.E. extract (400 mg/kg). The first 3 weeks animals were supplemented with HFD, and the last 3 weeks animals were supplemented with HFD along with atorvastatin (10 mg/kg) or S.E. extract (200 and 400 mg/kg). It was observed that mice of the HFD control group showed a significant rise in the total cholesterol, triglycerides, LDL-C, and VLDL-C levels and a notable decrease in HDL-C levels. In addition, a consequential increment in ECG parameters such as QT or QTc and RR interval and a noteworthy decline in the heart rate were observed in HFD control mice. Treatment with S.E. extract (200 and 400 mg/kg) showed a significant improvement in the lipid profile. Moreover, the extract also significantly normalized the prolonged QT or QTc and RR interval and the heart rate in HFD-challenged mice. Hence, we can conclude that S.E. extract encumbers the prolongation of QT or QTc and RR interval and increased the heart rate in HFD-challenged mice.